PENGARUH DIMENSI KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KINERJA PEGAWAI BALAI KARANTINA IKAN, PENGENDALIAN MUTU DAN KEAMANAN HASIL PERIKANAN MEDAN I - Amiruddin Ritonga; Humaini Nasution; Aswiluddin .; Sry Liswati (Manajemen dan Bisnis, 2021)
The formulation of the problem in this study are: How much influence the knowledge, skills and abilities have on employee performance. This study aims to determine the effect of knowledge, skills and abilities on employee performance. Taking  the  sample  using  total  sampling  technique,  the  sample  of  this  study amounted to 37 people. Knowledge  partially has a positive effect on employee performance;  Skills  partially  have  a positive  effect  on employee  performance; Ability partially has a positive effect on employee performance; Knowledge, skills and abilities have a positive and significant impact on employee performance Fish Quarantine Center, Quality Control and Safety of Fishery Products I.